Síntese e caracterização de compósitos multiferroicos de manganita La: Sr e titanatos de Ba e Sr - Paranhos, Rafael Rodrigo Garofalo (2011)
In this paper, we seek to prepare composite multiferroics extrinsic whose potential for technological applications, especially in the electronics industry, and the possibility of new phenomena of fundamental scientific interest made the subject multiferroics has attracted attention and efforts of the scientific community. Such composites have in its constitution the combination of ferroelectric barium titanate, strontium titanate in paraelectric and the ferromagnetic lanthanum-strontium manganite. This choice is due to the interesting magnetic properties of manganites and its strong coupling between the magnetic properties, electrical and estrututrais, leading to the occurrence of giant magnetostrição [1]. The ferroelectric chosen has a structure compatible with that of the manganite. Moreover, the possibility of adjusting the ferromagnetic transition temperature of the manganite, through chemical doping could make room for the optimization of their properties at room temperature. The synthesis method chosen was the Pechini chemical route, featuring good conditions of uniformity in their characteristics and the final conformation of the specimen was (0-3) For the characterization of the samples was proposed a protocol starting from the structural characterizations and chemical profiles using X-ray diffraction, microstructural through the electron microscope using a high-resolution physical characterizations of relative density, resistivity, dielectric and ferroelectric properties and, finally, analysis of magnetoelectric coupling. The results that deserve mention are the correct phase formation in composite materials and a good densification of the bodies of evidence, above 90%. We can observe the deterioration of electrical properties in composite materials